Pharmacokinetic and pharmacodynamic features of nanoemulsion following oral, intravenous, topical and nasal route - Chowdhury, Hira; Gorain, Bapi; Chatterjee, Bappaditya; Mandal, Uttam Kumar; Sengupta, Pinaki; Tekade, Rakesh (Bentham Science, 2017)
Abstract: Background: Most of the active pharmaceutical ingredients discovered recently in pharmaceutical field exhibits poor aqueous solubility that pose major problem in their oral administration. The oral administration of these drugs gets further complicated due to their short bioavailability, inconsistent absorption and inter/intra subject variability. Methods: Pharmaceutical emulsion holds a significant place as a primary choice of oral drug delivery system for lipophilic drugs used in pediatric and geriatric patients. Pharmacokinetic studies on nanoemulsion mediated drugs delivery approach indicates practical feasibility in regards to their clinical translation and commercialization. Results: This review article is to provide an updated understanding on pharmacokinetic and pharmacodynamic features of nanoemulsion delivered via oral, intravenous, topical and nasal route. Conclusion: The article is of huge interest to formulation scientists working on range of lipophilic drug molecules intended to be administered through oral, intravenous, topical and nasal routes for vivid medical benefits. Keywords: Hydrophobicity, oral delivery, pharmacokinetics, pharmacodynamics, routes of administration.